Impact of Bobath Based Rehabilitation Program and Conventional Physiotherapy: Children with Hydrocephalus - Tanpreet Kaur Bakshi; Jaspreet Singh Vij; Ashish Chhabra (Анналы клинической и экспериментальной неврологии)
Introduction. Hydrocephalus is an abnormal enlargement of the brain ventricles caused by increased amounts of cerebrospinal fluid. The aim of the study was to determine the efficacy of Bobath Based Rehabilitation Program and conventional physiotherapy for improving motor function in children with hydrocephalus and reducing levels of anxiety in parents of children with hydrocephalus.